Neonatal striped hyperpigmentation of the torso secondary to split lines of the horny layer at birth. - Bonifazi, E.; Cutrone, M. (European Journal of Pediatric Dermatology, 2011)
Case report. A newborn baby of Nigerian origin was observed in the first day of life due to the presence of an ich-thyosiform skin. The baby was the firstborn of non consanguineous parents, born at term from natural childbirth and his family history was negative for ichthyosis. The physical examination showed a dry skin, similar to collodion: on the thoracoabdominal wall there were scaly whitish horizontal lines that seemed to originate from a split of the horny layer (Fig. 1). A paraphysiological hyperpigmentation of the scrotum and distal phalanges of hands was also evident (Fig. 2, 3). These clinical features led to the diagnosis of collodion baby and emollient therapy was prescribed. 15 days later on control examination the ichthyosiform skin had regressed and the split lines of the horny layer had been replaced by hyperpigmentation lines that perfectly reproduced the pattern of the previous lesions (Fig. 2); very similar hyperpigmentation lines were also evident on the volar surface of the forearms (Fig. 4). The final diagnosis was transitory neonatal striped hyperpigmentation of the torso and the baby's mother was reassured on their regression in months.